Varovná bolest stehna - vzácný a včasný projev drobného vysoce agresivního synoviálního sarkomu - Navrátil, Luděk; Chudáček, Zdeněk; Mírka, Hynek; Hes, Ondřej (Bolest (Praha, Print), 2009)
Aim: Synovial sarcoma is a clinically and morphologically distinct neoplasm of uncertain histogenesis predominantly affecting the extremities of adolescents and young adults. It is the fourth commonest soft tissue sarcoma in adults. It is regarded as an aggressive neoplasm with a reported 5-year survival rate ranging from 40-76%. The aim of our presentation is to verify the unusual presentation of long-standing pain at the site of a deep small tumour, without the development of swelling. Patients - methods and results: An 18-year-old young man suffered with localised pain in the medial lower part of the right thigh for 5 years. The pain appeared after prolonged exercise (cycling), and worsened with palpation. He had no pain at rest. There was no palpable mass in the thigh. A small spherical lesion was diagnosed as an obliterated venous varix one year prior to admission for an MRI. A small deep localised tumour was revealed by an ultrasonography and MRI shortly before surgery. Surgical excision was performed using preoperative ultrasonography. A solid 1 cm diameter demarcated tumour was removed from the deep inter-muscular septum. Surprisingly, the histological diagnosis of a monophasic synovial sarcoma was established. Thus the reoperation of the surgical margin excision was indicated. No malignant cells were found in the excised soft tissues. The patient is alive and well 1 year after the surgery. The controlled MRI of the thigh did not reveal any signs of a viable tumour. Discussion: The occurrence of long-standing pain at a tumour site prior to the development of swelling is uncommon. The pathophysiology of this pain is unclear. Awareness of this unusual presentation and appropriate investigation may enable the detection of synovial sarcoma at an early prognostically favourable stage.
Keywords: Pain; Thigh; Magnetic Resonance Imaging; bolest; lidé; synoviom; mužské pohlaví; Young Adult; Male; magnetická rezonanční tomografie; Sarcoma, Synovial; stehno; mladý dospělý; Humans